1984
DOI: 10.3171/jns.1984.60.2.0335
|View full text |Cite
|
Sign up to set email alerts
|

Significance of contrast enhancement in cranial computerized tomography after subarachnoid hemorrhage

Abstract: Eighty patients with subarachnoid hemorrhage underwent computerized tomography (CT) scanning before and after administration of Conray contrast medium. Abnormal enhancement was seen in visual evaluation of the CT scans in 26 cases, in the regions bordering the subarachnoid spaces. Abnormal enhancement was associated with a poor clinical condition, angiographic spasm, and a poor outcome. Measurements of absorption values in the thalamus revealed significant increases in density after contrast enhancement in tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…33,54,57 It is well known that leukocyte trafficking increases in SAH due to a breakdown of the blood-brain barrier. 5,[8][9][10][11]14,23,52,66 Increased levels of various soluble adhesion molecules (such as E-selectin, intercellular adhesion molecule-1, and vascular adhesion molecule-1) and cytokines (such as IL-6 and IL-1) have been noted in the plasma and CSF of patients with SAH.…”
Section: Discussionmentioning
confidence: 99%
“…33,54,57 It is well known that leukocyte trafficking increases in SAH due to a breakdown of the blood-brain barrier. 5,[8][9][10][11]14,23,52,66 Increased levels of various soluble adhesion molecules (such as E-selectin, intercellular adhesion molecule-1, and vascular adhesion molecule-1) and cytokines (such as IL-6 and IL-1) have been noted in the plasma and CSF of patients with SAH.…”
Section: Discussionmentioning
confidence: 99%
“…2223 The clinical significance of BBB breakdown after SAH has been stressed, and a correlation between BBB opening, poor neurologic grade, and outcome has been reported. 7 In an attempt to elucidate the pathochemical mechanism of BBB dysfunction after SAH, we tested the hypothesis that BBB opening is induced by the action of lipid hydroperoxides generated from free radical reactions catalyzed by iron and by hemoglobin degradation products and by the oxidative catabolism of arachidonic acid. Lipid hydrolysis with subsequent eicosanoid production may also be a pathochemical event occurring early after SAH.…”
Section: Discussionmentioning
confidence: 99%
“…6 An increase in the permeability of major cerebral vessels and microvessels following subarachnoid hemorrhage (SAH) has been reported in both humans and experimental animals and has been correlated with a poor clinical outcome. 7 Although increased intracranial pressure (ICP), changes in cerebral blood flow (CBF), and loss of CBF autoregulation contribute to the breakdown of the BBB, 1 vasoactive substances originating from the breakdown products of extravasated blood also contribute to the opening of the BBB by directly affecting the brain vessels.…”
Section: Protective Effect Of a 21-aminosteroid On The Blood-brain Bamentioning
confidence: 99%
“…In this case, as it appeared that the brain metastasis might have followed the SAH, we speculated that the SAH might have been involved. Under experimental conditions, previous studies have found that SAH causes marked damage to the blood-brain barrier (BBB) in cat and rat models, and that it induces disruption of the BBB (11)(12)(13)(14)(15)(16)(17). For example, Trojanowski used Evans blue to detect discrete, diffuse spots in the cerebral cortex an hour after the occurrence of an SAH.…”
Section: Discussionmentioning
confidence: 99%